Knowledge, attitudes, and practices of healthcare providers toward ADR reporting regarding thiopurine drugs for the treatment of acute lymphoblastic leukemia at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Kassa, Eyuel; Birhan, Mastewal; Ayalew, Mulugeta; Gelaw, Aschalew; Gidey, Abdulkader Mohamedsaid; Tilahun Worku, Degalem; Mekonen, Awole; Teklehaimanot, Ermias; Asnakew, Assefa; Amare, Alazar; Berhane Tessemma, Nega (Frontiers in Pharmacology, 2025)
BackgroundKnowledge, attitudes, and practices (KAP) regarding the use of thiopurine chemotherapeutic drugs in the treatment of acute lymphoblastic leukemia (ALL) are critical for healthcare professionals. Thiopurines are associated with varying levels of toxicity, including myelosuppression, hepatotoxicity, and gastrointestinal intolerance. Approximately 20% of ALL patients discontinue thiopurine therapy due to toxicity and other adverse events. This study aims to assess the KAP of healthcare providers (HCPs) concerning thiopurine drugs used in the treatment of ALL in hospital wards in Northwestern Ethiopia.MethodsA hospital-based cross-sectional study was conducted among 161 HCPs at the University of Gondar Comprehensive Specialized Hospital from June 1, 2023, to August 30, 2023. Data were collected using a self-administered questionnaire. The collected data were coded, entered and analyzed using SPSS version 25. Associations between categorical variables were assessed using cross tabulation, and both crude and adjusted odds ratios were calculated with a 95% confidence interval. Variables with p-values less than 0.05 were considered statistically significant.ResultsA total of 161 HCPs participated in the study, comprising 69 (42.9%) females and 92 (57.1%) males. The majority of participants were nurses 105 (65%), followed by physicians 20 (12.4%), pharmacists 19 (11.8%), midwives 10 (6.2%), and health officers 7 (4.3%). More than half of the participants demonstrated inadequate knowledge 94 (58.4%), negative attitudes 82 (50.9%), and poor practices 90 (55.9%) regarding the use of thiopurine drugs for the treatment of ALL. Approximately 50 (31.1%) participants understood the term “thiopurine drugs,” while 89 (55.3%) were aware of their adverse drug reactions. However, the majority 136 (84.5%) had not received training on how to report adverse drug reactions.ConclusionThe majority of healthcare professionals demonstrated negative attitudes, inadequate knowledge, and poor practices concerning the reporting of adverse drug reactions associated with thiopurine drugs.